The Relation Between the Metopic Suture Persistence and Frontal Sinus Volume and Olfactory Fossa Depth: A Reliability Study with Semiautomatic Volume Measurement - Başak Atalay; Mehmet Bilgin Eser (Medeniyet Medical Journal)
Objective: This study aims to investigate the relationship of the persistence of metopic suture (PMS), frontal sinus volume (FSV), and olfactory fossa depth (OFD). Methods: Tomography scans of 1,603 patients aged 18-65 years were evaluated for the presence of PMS. In the study, 74 PMS cases and 74 controls were included. The appearance of each individual’s frontal sinus was classified as aplasia, hypoplasia, or normal. Two observers independently measured the lateral lamella length (LLL), OFD, and FSV. Interobserver agreement was evaluated with the intraclass correlation coefficient (ICC) and Cohen’s kappa coefficient (κ). Results: The prevalence of PMS was found to be 4.99% [95% confidence interval (CI): 4.03-6.17]. The PMS group had five times higher hypoplasia/aplasia than the controls (52.70%, 95% CI: 41.48-63.66 and 10.81%, 95% CI: 5.58-19.91, respectively; p<0.001). An “almost perfect” agreement was detected among observers for the frontal sinus appearance classification: κ=0.807, p<0.001. The ICC of continuous measurements for OFD, LLL, and FSV, respectively, presented “excellent” reliability: 0.956, 0.958, and 0.981, with p<0.001 for each. LLL was shorter, OFD was shallower, and FSV was smaller in the PMS group than the control group (p<0.001). There was a moderate positive correlation between OFD, LLL, and FSV (r=0.306, r=0.302). Conclusions: This study interprets that the presence of PMS is related frontal sinus development and volume. With PMS, a smaller FS, shorter lateral lamella, and shallower olfactory fossa may be expected.